2007
DOI: 10.1038/sj.ejcn.1602738
|View full text |Cite
|
Sign up to set email alerts
|

Variation of major neutral oligosaccharides levels in human colostrum

Abstract: Objectives: Human colostrum is known to be important for the protection of infants against infection by pathogenic microorganisms. This protection is thought to be due, partially, to various neutral and acidic oligosaccharides that are present in colostrum and milk. However, the concentrations of each of the oligosaccharide of human colostrum have not yet been determined. The aim of this present study was to determine the concentration of each of the major neutral oligosaccharide for three consecutive days fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 36 publications
(33 reference statements)
6
114
1
Order By: Relevance
“…and Gal(b1 -3)GlcNAc(b1 -3)Gal(b1 -4)Glc (lacto-Ntetraose (LNT)) constitute from one-quarter to one-third of the total HMOs (Asakuma et al, 2008).…”
Section: Evolution Of Milk Oligosaccharides and Lactosementioning
confidence: 99%
“…and Gal(b1 -3)GlcNAc(b1 -3)Gal(b1 -4)Glc (lacto-Ntetraose (LNT)) constitute from one-quarter to one-third of the total HMOs (Asakuma et al, 2008).…”
Section: Evolution Of Milk Oligosaccharides and Lactosementioning
confidence: 99%
“…2 fucosyllactose (2 FL), 3 fucosyllactose (3 FL), Lacto N tetraose (LNT), Lacto N fucopentaose I (LNFP I), Sialyllacto N tetraose (LSTc), 3 sialyllactose (3 SL) and 6 sialyllactose (6 SL) were purchased from Dextra Laboratories (England). 4 Galactosyllactose (4 GL) and 6 galactosyllactose (6 GL) were obtained from Dr. Tadashi Nakamura (Obihiro University); their purities were checked by high performance liquid chromatography (HPLC) after pyridylamination prior to the successive study 29) and were found to be 83.8 and 71.8% pure, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Human colostrum samples were collected in Keiai Hospital from twenty four healthy mothers during the first 3 days of lactation, as previously described. 29) We obtained informed consent from all the donors to use their samples, using the protocol approved by Obihiro University of Agriculture and Veterinary Medicine.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations